Strategi Guru Aqidah Akhlak Dalam Membentuk Akhlak Al-Karimah Siswa Kelas VI di MI Al-Ijtihad Al-Mahsuni Jontak - Ansori, Sopian; Kurnia, Wawan; Indra Saputra, Ramadhani (Adaara: Jurnal Manajemen Pendidikan Islam, 2024)
This research was conducted with the aim of finding out how the Aqidah Akhlak teacher's strategy was in shaping the morals of class VI students at MI Al-Ijtihad Al-Mahsuni Jontak and describing the supporting and inhibiting factors of the teacher's strategy for forming the morals of class VI students of al-Karimah. at MI Al-Ijtihad Al-Mahsuni Jontak. This research is a descriptive qualitative research, by trying to describe the research results obtained in the field. Data collection techniques that researchers use are in the form of observation, interviews and documentation. As for data analysis using qualitative analysis techniques, consist of three components of activities that are interrelated with one another, namely data reduction, data display, and drawing conclusions. The findings in the Aqidah Akhlak teacher strategy research in shaping the morals of al-karimah grade VI students by applying: exemplary, giving advice, providing motivation and supervision. In implementing this strategy, there are supporting factors such as: There is cooperation between teachers in schools and motivation and support from both parents or guardians of students. While the inhibiting factors are: lack of control by parents or guardians of students over students who use social media and environmental factors.